DOI: 10.22215/etd/2018-13343
|View full text |Cite
|
Sign up to set email alerts
|

Two Floods, A Wildfire, and A Hurricane: The Role of the Canadian Armed Forces in Emergency Management

Abstract: The role of the Canadian Armed Forces (CAF) during domestic disaster response has increased significantly over the last century due to the military's response capacity and the increased frequency and impact of natural hazards. However, there has been no systematic academic assessment of how effectively CAF is integrated into the civilian emergency management system, particularly during the response phase. Using archival analysis and interviews with senior CAF officers and civilian officials, this study fills t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 118 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Studies have identified factors influencing successful collaboration, such as clear communication channels, shared resources, and mutual trust and respect among stakeholders. One notable example of cross-jurisdictional collaboration is the partnership between the USA and Canada in managing shared natural hazards, such as wildfires and floods (Botha, 2018;Adebayo, 2022). Research has shown that this collaboration has led to improved information sharing, joint planning and training exercises, and coordinated response efforts during disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have identified factors influencing successful collaboration, such as clear communication channels, shared resources, and mutual trust and respect among stakeholders. One notable example of cross-jurisdictional collaboration is the partnership between the USA and Canada in managing shared natural hazards, such as wildfires and floods (Botha, 2018;Adebayo, 2022). Research has shown that this collaboration has led to improved information sharing, joint planning and training exercises, and coordinated response efforts during disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This view is also supported and highlighted in the professional literature in the emergency management field, as well as textbook chapters (B. D. Phillips et al, 2016;Rodríguez et al, 2007;Thomas et al, 2009). Within the literature on emergency management, the outlined relationships and communications have been evaluated in dissertations (Botha, 2018;Martini, 2014;Plance, 2018), and a considerable body of scholarly work on emergency preparedness (Kohn et al, 2012;Levac et al, 2012) supports the following hypotheses:…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
“…Policy formulation specific to this subfield follows this inclusionary theoretical model of multiple streams and structures, with several important voices. It is important to understand the methodologies used by governments to identify issues and develop policies -specifically in a multi-level governance structure such as emergency management within Canada (Botha, 2018), which follows a predictable path outside immediate events, similar to normal policy operations (Henstra, 2010(Henstra, , 2011.…”
Section: Creation Of Public Policymentioning
confidence: 99%